LEARNING FROM NEWS: IS ONLINE BETTER THAN PRINT? - Omar, Bahiyah (2015)
This study compares the process of learning from news between print and online news environments. The study adopts the framework of Cognitive Mediation Model that treats surveillance motivation as the cause of news orientation and news elaboration which in turn are the causes of knowledge acquisition. To identify the differences in news learning between print and online media, a “between-subjects” experiment was used. The study tested the two models using Structural Equation Modelling (SEM). The results show that both print and online models are supportive of the Cognitive Mediation Model. While most of the hypothesized relationships were supported, the study found that orientation in information space has significant effect on knowledge level of print but not online readers. This result suggests the disadvantages of Web non-linearity on learning outcome. The study also found that the mediating role of news orientation was only supported in the print model. The higher R2 value for print compared to online model suggests the influential role of traditional print in news learning.